Dampak Pelatih Berlisensi terhadap Peningkatan Prestasi Sekolah Sepak Bola Mitra Persada Cilongok Banyumas - Didi Wakhyudi; Iif Firmana (Mutiara Pendidikan dan Olahraga, 2026)
This study is motivated by the important role of licensed coaches in implementing the Filanesia curriculum to improve the quality of early-age football development. The purpose of this study is to examine and analyze the significance of the impact of training programs implemented by licensed coaches on the improvement of holistic performance (technical, tactical, physical, and mental aspects) of students at the Mitra Persada Football School (SSB) in Cilongok, Banyumas. The method used in this study is a quantitative experimental approach with a Pre-Experimental Design, specifically the One-Group Pretest-Posttest Design. The population consisted of 25 students from the Mitra Persada Football School aged 13–15 years. The sampling technique used was purposive sampling, resulting in a final sample of 15 students. Data collection instruments included performance tests and questionnaires that had been validated by experts with a feasibility level of 95% (categorized as “Very Feasible”). The collected data were analyzed using the Paired Sample T-Test and N-Gain Score effectiveness test with the help of SPSS version 26. The results showed an overall improvement in performance, with the average pretest score of 58.40 increasing to 79.20 in the posttest. The Paired Sample T-Test results indicated a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that H0 was rejected and Ha was accepted. Furthermore, the effectiveness test using the N-Gain Score resulted in a value of 0.50 (50%), which falls into the “Moderate” or fairly effective category. Thus, it can be concluded that there is a positive and highly significant impact of licensed coach training programs on improving the performance of early-age athletes at SSB Mitra Persada Cilongok Banyumas.